Active pixel sensors in high-voltage CMOS technologies for ATLAS - Peric, Ivan (Journal of Instrumentation, 2012)
High-voltage particle detectors in commercial CMOS technologies are a detector family that allow implementation of low-cost, thin and radiation-tolerant detectors with a high time resolution. Their unique property is that the pixel electronic is embedded inside the sensor diodes. For this reason, we refer to this detector type as the "smart diode” array — SDA. In the proof-of-principle phase of the development, we have demonstrated a radiation tolerance of 10 15 n eq /cm 2 , nearly 100% detection efficiency and a spatial resolution of about 3 μm. Thanks to its high radiation tolerance, the SDA technology represents an interesting option for sLHC upgrades or CLIC detector readout. In order to test the concept, within ATLAS-upgrade R&D, we are currently studying an active pixel detector demonstrator HV2FEI4, implemented in AMS 180 nm high-voltage process. The contacts between the detector- and readout chip can be established either capacitively or by bump-bonding.
Gesehen am 18.07.2018